First observation of the decay B0 → D*+D*- - Artuso, M; Dambasuren, E; Kopp, S; Moneti, G; Mountain, R; Schuh, S; Skwarnicki, T; Stone, S; Titov, A; Viehhauser, G; Wang, J; Csorna, SE; et al. (1999)
We have observed four fully reconstructed B0 → D*+D*- candidates in 5.8 × 106 Υ(4S) → BB̄ decays recorded with the CLEO detector. The background is estimated to be 0.31 ± 0.10 events. The probability that the background could produce four or more signal candidates with the observed distribution among D*+ and D*- decay modes is 1.1 × 10-4. The measured decay rate, B(B0 → D*+D*-) = [6.2-2.9+4.0(stat) ± 1.0(syst)] × 10-4, is large enough for this decay mode to be of interest for the measurement of a time-dependent CP asymmetry. © 1999 The American Physical Society.